2022
DOI: 10.1063/5.0097282
|View full text |Cite
|
Sign up to set email alerts
|

Temporal structure of blobs in NSTX

Abstract: The time dependence of the blob pulse shape and the waiting time between blobs was found using data from the gas puff imaging diagnostic in NSTX. The database used was of 103 shots from 2010 as described in a previous paper (Zweben et al., Phys. Plasmas 29, 012505 (2022).]. The blob pulse shape was well fit by an exponential rise and fall where the average rise time was τr = 9.0 ± 2.7  μs and the average fall time was τf = 16.6 ± 5.8  μs. The waiting times between blob pulses above a threshold of three times t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Frontiers in Nuclear Engineering frontiersin.org revealing intermittent blob-like structures ejected from a source region, see Figure 2. While reminiscent of observations of the structure and motion of edge turbulence and "blobs" in experiments (Zweben et al, 2022), direct comparisons in this edge region remain as exciting future work. One goal of validation in fusion is to develop reliable models that can be used to predict performance in future devices.…”
Section: Validation Of Turbulence Transport Models For Fusion Energymentioning
confidence: 95%
“…Frontiers in Nuclear Engineering frontiersin.org revealing intermittent blob-like structures ejected from a source region, see Figure 2. While reminiscent of observations of the structure and motion of edge turbulence and "blobs" in experiments (Zweben et al, 2022), direct comparisons in this edge region remain as exciting future work. One goal of validation in fusion is to develop reliable models that can be used to predict performance in future devices.…”
Section: Validation Of Turbulence Transport Models For Fusion Energymentioning
confidence: 95%
“…It was found in [31][32][33] that such 'bumps' can emerge on the closed flux surfaces and then they may propagate across the separatrix into the SOL plasma, which demonstrates once more the nonlocality of the SOL plasma transport.…”
Section: Special Features Of Cross-field Plasma Transport In the Sol ...mentioning
confidence: 99%
“…Single-point measurements record the filaments as an asymmetric, two-sided exponential pulse function. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] The radial filament velocity depends on the blob size and amplitude as well as plasma parameters and takes a wide range of values. This dependence has been extensively explored theoretically and by numerical simulations of isolated filament structures in various plasma parameter regimes.…”
Section: Introductionmentioning
confidence: 99%
“…In previous experimental investigations based on second-long, single-point measurement data time series, the fundamental statistical properties of the plasma fluctuations in the far SOL have been identified. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] It has been demonstrated that the fluctuations can be described as a superposition of uncorrelated, exponential pulses with an exponential distribution of pulse amplitudes, referred to as a filtered Poisson process. [96][97][98][99][100][101][102][103] For such a stochastic process, the probability density function is a Gamma distribution with the scale parameter given by the average pulse amplitude and the shape parameter given by the ratio of the average pulse duration and waiting times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation